Exploring the factors that contribute to tax compliance in Malaysia - Ku Ahmad, Ku Ahmisuhaiti; Hassan, Rahayu; Shaikh Mohammad, Siti Nor Syahira (Faculty of Accountancy, 2025)
Tax collection contributes more than 50% of the Malaysian government revenue and is considered the main source of income in Malaysia (Nor Aziah 2023; Norul et al. 2021 ). There are two categories of tax administration in Malaysia, namely direct taxes and indirect taxes. The Inland Revenue Board (IRB) is responsible for collecting direct taxes, while the Royal Malaysian Customs (RMC) handles indirect tax collection. The revenue collected from these two types of taxes is the main source and important instrument of government revenue. According to Hakim (2024), revenue collected from taxpayers, especially by authorities such as the IRB, is important for the development and stability of Malaysia.